Maternal attachment state of mind and defensive functioning in pregnancy: predicting mother–infant relationship at 6 months through the PDM-2 Infancy and Early Childhood section - Carone, Nicola; Tracchegiani, Jacopo; Lingiardi, Vittorio (Frontiers in Psychology, 2025)
BackgroundPregnancy is a period of profound psychological reorganization, marked by increased vulnerability and the reactivation of past attachment experiences. During this transition, maternal attachment states of mind and the ability to regulate emotional distress through unconscious defenses play a crucial role in shaping early mother–infant relationships. Although the Psychodynamic Diagnostic Manual, second edition (PDM-2) was not designed as a parenting manual, it provides a valuable framework for assessing how maternal attachment and defensive functioning influence the mother–infant relationship, since it emphasizes defensive functioning as a core component of mental functioning.AimsThis longitudinal study examines the relationship between maternal attachment mental states during the third trimester and mother–infant relationship quality at 6 months postpartum, while also exploring the mediating role of maternal defensive functioning.MethodsA community sample of 68 cisgender heterosexual pregnant women (Mage = 35.83 years; SD = 4.32) was recruited during the third trimester (Time 1 [T1]; Mgestational age = 36.30 weeks, SD = 1.80). At T1, maternal attachment coherence of mind was assessed using the Adult Attachment Interview (AAI), and defensive functioning was evaluated applying the Defense Mechanism Rating Scale–Q sort to AAI transcripts. At 6 months postpartum (Time 2 [T2]), the mother–infant relationship quality was assessed using the Infant–Caregiver Relationship Scale, as detailed in Section IV of the Psychodiagnostic Chart—Infancy and Early Childhood from the PDM-2. At T2, 58.82% of infants were assigned female at birth, with a mean age of 6.04 months (SD = 0.34). All participating mothers resided in Italy and were partnered with their infants’ fathers.ResultsMediation analysis showed that greater prenatal attachment coherence of mind was directly associated with better mother–infant relationship quality. Furthermore, mother–infant dyads in which mothers exhibited lower AAI coherence of mind demonstrated poorer relationship quality via less adaptive maternal defensive functioning.ConclusionMaternal attachment mental states and defensive functioning during pregnancy play critical roles in the development of early caregiving relationships. The findings also highlight the PDM-2’s relevance in understanding maternal mental functioning and emphasize the need for targeted parenting interventions during pregnancy and early postpartum.